Isoniazid plus sulphadoxine-pyrimethamine can reduce morbidity of HIV-positive patients treated for tuberculosis in Africa: a controlled clinical trial - Haller, Louis; Sossouhounto, Raoul; Coulibaly, Issa M.; Dosso, Mireille; Kone, Moussa; Adom, Hilaire; Meyer, Urs A.; Betschart, Bruno; Wenk, Markus; Haefeli, Walter E.; Lobognon, Legré R.; Porquet, Michel; et al. (Chemotherapy, 1999)
An annual 20% excess mortality rate is observed in HIV-seropositive patients after treatment for tuberculosis. An affordable secondary prophylaxis against main opportunistic diseases is needed, i.e. against tuberculosis, toxoplasmosis, pneumocystosis and other infections occurring in this target population. This open prospective randomized study assessed morbidity and mortality in 2 cohorts of HIV-seropositive patients having recently recovered from pulmonary tuberculosis: 134 patients assigned to prophylactic treatment with isoniazid (INH, 300 mg once daily) plus sulphadoxine-pyrimethamine (S, 500 mg/P, 25 mg once weekly), and 129 were controls, comparable for sex, age, weight and HIV-serology. Patients were followed-up for up to 2 years: 192 person-years (PY) in the prophylaxis group and 142 PY in the control group. Four patients developed tuberculosis and 20 patients died in the prophylaxis group, compared to 10 and 23 controls, respectively. Sick days were reported by 22 patients in the prophylaxis group and by 77 patients in the control group. This prophylaxis was associated with a moderate decrease of mortality (log rank test: p = 0.1736), a significant decrease of tuberculosis incidence (log rank test: p = 0.0234), a highly significant reduction of adverse events and sick days, and a prevention of wasting (p = 0.008) and anaemia (p = 0.045). No death from toxoplasmosis occurred in the prophylaxis group as compared to 2 possible cases among controls; toxoplasmosis IgG levels declined in treated patients, but increased in controls (p = 0.01). There was no adverse drug reaction due to SP (10,006 doses) or to INH. Compliance with SP intake was good, but moderate as with INH intake. We conclude that a secondary prophylaxis with INH+SP represents a cost-effective measure to improve health conditions of HIV-infected adults in Côte d’Ivoire, following a full treatment course against tuberculosis.